Smoking cessation and exercise: perspectives from smokers with and without mental health problems - Schöttl, Stefanie E.; Scheibner, Laura; Frühauf, Anika; Kopp-Wilfling, Prisca; Edlinger, Monika; Holzner, Bernhard; Kopp, Martin (Frontiers in Public Health, 2025)
IntroductionSeveral smoking cessation methods are available, but the approaches were originally developed for the general population and are often applied to people with mental health problems. To address the needs of smokers with and without mental health problems for an exercise-assisted smoking cessation program, it seems necessary to know more about potentially different perspectives on what prevents them from quitting, how to increase motivation to quit, and how such a program is perceived.MethodsIn this study, an online survey was conducted to assess preferences for an exercise-assisted smoking cessation program, reasons for smoking, barriers, motives, and need of support for quitting smoking. A total of 257 smokers took part in the study, 82 reported mental health problems.ResultsIn addition to significant differences in sociodemographic and smoking-related characteristics between smokers with and without mental health problems, regression analyses revealed that factors such as age, BMI, and confidence in quitting were associated with smoking cessation behavior in the total sample. Significant differences were found between the two groups in their reasons for smoking, barriers, motives, and support for quitting. While both groups preferred an exercise-assisted smoking cessation program to last 10–11 weeks with a frequency of 2 to 3 days a week, smokers with mental health problems favored shorter exercise sessions and would choose walking or dancing as helpful exercise.ConclusionDue to different addiction-related variables and preferences, a special smoking cessation program combined with exercise for smokers with mental health problems should be developed and tested for effectiveness in clinical trials.